The Brilliant Socrates and the Foundation of Western Philosophy - Baby Professor (London, United States, Baby Professor, 2017)
Who was Socrates and why do scholars still look up to him until this day? This man hasn't been around for hundreds of years; and yet, he is still very much alive in books. Modern-day arguments are based on his words. His teachings remain true despite the changes in technology and beliefs. If you're curious, open this book and get to know the man named Socrates!
Keywords: Biography -- Biography